The obesity-asthma link in different ages and the role of Body Mass Index in its investigation: findings from the Genesis and Healthy Growth Studies - Guibas, G. V.; Manios, Y.; Xepapadaki, P.; Moschonis, G.; Douladiris, N.; Mavrogianni, C.; Papadopoulos, N. G. (Allergy, 2013)
To date, an obesity/asthma link is well defined in adults; however, the nature of such a link is obscure in children, partly due to Body Mass Index (BMI) limitations as a surrogate fat mass marker in childhood. We thus opted to investigate the association of adiposity with asthma in children of different ages, using several indices to assess fat mass.|Wheeze ever/in the last 12 months (current) and physician-diagnosed asthma were retrospectively reported via questionnaire by the parents of 3641 children, participating in two cross-sectional studies: 1626 children aged 2-5 (the Genesis Study) and 2015 children aged 9-13 (the Healthy Growth Study). Perinatal data were recorded from the children's medical records or reported by parents. Anthropometric measurements (i.e., BMI, waist/hip circumference, biceps/triceps/subscapular/suprailiac skinfold thickness) were conducted in both cohorts; bioelectric impedance analysis (BIA) was conducted only in preadolescent children.|In children aged 2-5, asthma was positively correlated with conicity index, waist/hip circumference, waist-to-height ratio, skinfold thickness, and skinfold-derived percentage fat mass (P < 0.05) but not BMI or BMI-defined overweight/obesity, after adjusting for several confounders. In children aged 9-13, asthma was positively associated with conicity index, waist circumference, waist-to-height ratio, skinfold thickness, skinfold-derived percentage fat mass, BIA-derived percentage fat mass, BMI, and BMI-defined overweight/obesity, following adjustment (P < 0.05). Current/ever wheeze was not consistently associated with fat mass in either population.|Fat mass is positively linked to asthma in both 2-5 and 9-13 age spans. However, the failure of BMI to correlate with preschool asthma suggests its potential inefficiency in asthma studies at this age range.